Metode Pendidikan Islam dalam Penanggulangan Penyalahgunaan Narkoba bagi Remaja di Pondok Remaja Inabah Suryalaya Tasikmalaya - Mukri, Syarifah Gustiawati; Rosyadi, A. Rahmat; Saefuddin, Didin (Ta’dibuna: Jurnal Pendidikan Islam, 2015)
The drug abuse in Indonesia is becoming worse, which is indicated by the more abusers as the victims. Globalisation era easily enables people gain their necessities; drug as one of those tempting; especially the young generations, which makes them as the addicts. The worst thing of being an addict is that he tends to violate the norms in societies even the laws. A drug abuser is anybody uses drugs without any legal rights and against the laws, while an addict is anyone misuses and experiences addiction to the drugs either physically or psychologically. Islamic Boarding of Suralaya is a specific boarding for juvenile delinquency and drug addicts rehabilitation center. It was initiated by a moslem charismatic clergyman, KH. Shohibul Wafa Tajul Arifin who was during his life had contributed to the state and goverment in assisting to prevent the drug abuse in Indonesia. The Mental Rehabilitation center is named as Pondok Inabah which applies Inabah methods, by bathing, praying and dzikir (contemplating). This reaearch is a case study with a qualitative descriptive approach which focuses on the islamic methods of drug abuse prevention of juvenile and supported by primary and secondary sources of data. This research findings theoritically infer that the Inabah therapy method is islamic educational methods with spiritual approaches which are covered in an integratated, strictly and consistently applied curriculum; an effort to rehabilitate the drug abuse victims by tazkiyatun nafsi (individually purifying) in the practices of repentant bathe, prayers, and contemplation. Inabah theraphy, scientifically could be analogized as the sublimity theory in psychoanalysis by Sigmund Freud; by distracting negative energy/ libido urges to positive energy or decent deeds, which, he compared, is more productive to other mental defenses. This, yet differ with moslem psychologists such as Ibnu Sina-Avecina, Malik Badri, and Muhammad Utsman Najati who explained the importance of the spiritual dimension in reconciliating the addicts’ mentality, so that the practices of prayers and contemplation become the islamic sublimity methods. The results of the islamic education with spiritual approaches will provide a moslem an alternative solution in the efforts of preventing the drug abuse victims by rehabilitating the patients’ mentality to return to the paths of Allah’s SWT favour. Keyword: Inabah, Pendidikan Islam, Penyalahgunaan Narkoba, Remaja